CONCEPTUAL ASPECTS OF THE FORMATION OF THE KNOWLEDGE ECONOMY - Irina Iuryevna Glazkova; Dmitry Fedorovich Tsamalaidze (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes the experience of Russian and foreign authors who worked on the study of the ma- jor economic trends in the production and dissemination of knowledge, covers the main aspects of the knowledge economy: a new quality of economic growth, science and innovation, the development of networks, information and communications technology, knowledge-intensive services sector.